The Pedagogical Press of the 20-30-ies of the XX Century as a Source of the Study of the History of Childrenʼs Collective - Olena Saraeva (Pedagogical Discourse, 2013)
The pedagogical press as historical and pedagogical source is presented in the article through the prism of studying the problems of the history of a childrenʼs collective. The author carries out a structural-thematic analysis of scientific pedagogical publications «Ukrainian journal of reflexology and experimental pedagogy», «Way of education», «National teacher», «Friend of children», «Childrenʼs movement», and defines their decisive role in promoting and highlighting the main trends in educational policy in the USSR in the 20-30-th of XX century. In particular, it is established that in the press the problems of forming a childrenʼs collective were presented through the education of the leader of a group of children; the functioning of a childrenʼs collective in various childrenʼs organizations; the upbringing of conscious discipline as a mechanism of formation of a childrenʼs collective.